Position controlling of Sun Tracking System using optimization technique - Anuj Rawat; S. K. Jha; Bhavnesh Kumar (Energy Reports, 2020)
The prime objective of this paper is to devise optimization technique for the position control of Sun Tracking System (STS). In order to control the position of this system, PID controller tuned by different methods such as Genetic Algorithm (GA), Particle Swarm Optimization (PSO) and Teaching Learning Based Optimization (TLBO) is used. These methods have been carried out to determine the most optimized and robust one for the position control. The simulated results for nominal and perturbed value of servo amplifier gain show that the PID controller tuned with TLBO technique gives most optimized and robust performance in comparison to other tuning techniques.
Keywords: 330; Solar panel axis; Sun axis; Sun-Tracking System; Teaching Learning Based Optimization Algorithm